2003
DOI: 10.1016/s0021-9517(03)00144-1
|View full text |Cite
|
Sign up to set email alerts
|

Isomerization of n-butane and of n-pentane in the presence of sulfated zirconia: formation of surface deposits investigated by in situ UV–vis diffuse reflectance spectroscopy

Abstract: Catalytic performance and formation of carbonaceous deposits were studied simultaneously during alkane isomerization over sulfated zirconia in a fixed bed flow reactor with an optical window for in situ UV-vis diffuse reflectance spectroscopy. The reactions of n-butane (5 kPa) at 358 and 378 K and of n-pentane (0.25 kPa) at 298 and 308 K passed within 5 h or less through an induction period, a conversion maximum, and a period of deactivation; a steady activity of 41 and 47 µmol g -1 h -1 (isobutane formation) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The causes of their deactivation are still under discussion. The deactivation has been attributed to deposition of polymerized hydrocarbons on the catalyst, causing the coverage of the acid centers by carbonaceous deposits [29], to reduction of Zr 4+ to Zr 3+ on the surface of the catalysts during the reaction or to the transformation of tetragonal to monoclinic zirconia on the surface of the catalyst [30]. …”
Section: Resultsmentioning
confidence: 99%
“…The causes of their deactivation are still under discussion. The deactivation has been attributed to deposition of polymerized hydrocarbons on the catalyst, causing the coverage of the acid centers by carbonaceous deposits [29], to reduction of Zr 4+ to Zr 3+ on the surface of the catalysts during the reaction or to the transformation of tetragonal to monoclinic zirconia on the surface of the catalyst [30]. …”
Section: Resultsmentioning
confidence: 99%
“…It is therefore clear that the most important role of the Pt metal component is stabilizing the catalytic activity and to ensure higher selectivity for hydroisomerization. However, some general literature findings showed that the isomerisation activity of Zirconia catalysts declines rapidly at lower temperatures (Ahmad et al, 2003). This was reported to be attributed to formation of hydrocarbon surface deposits (coke), reduction of Zr 4+ to Zr 3+ by reacting hydrocarbon, H2S formation reduction of surface sulphate groups, and surface poisoning by water (Comelli et al, 1995;Li & Gonzalez, 1998;Vera et al, 1999).…”
Section: Galadima Et Al (Swj):15-22mentioning
confidence: 99%
“…Scheme and picture of an in-situ DRS cell for measuring solids operating in liquid-phase reactions at elevated temperatures and pressures. the in-situ DRS cells designed by Melsheimer et al [14,15]. Their cells allow the measuring of gas-phase reactions over catalytic solids in the range of 250-2500 nm, making use of a spacer to bridge the distance between integration sphere and microreactor.…”
Section: Fil-;mentioning
confidence: 99%